An integral equation for the external potential flow problem - Murid, Ali Hassan Mohamed; Nasser, Mohamed M. S.; Saidina Amin, Norsarahaida (Universiti Teknologi Malaysia, 2004)
A second kind Fredholm integral equation is is presented in this paper for the two-dimensional, irrotational, incompressible fluid flow around obstacles with smooth boundaries. It is shown that the integral equation obtained is still valid if the obstacle is an airfoil without a cusp trailing edge. The integral equation is solved using the Nystrom. The numerical results obtained show a good agreement with the exact solutions.